DAMPAK MASA KERJA, PENGALAMAN KERJA, KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN - Komang Nonik Jayanti; Komang Trisna Sari Dewi (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
global market, where a variety of businesses and companies are in it. To be able to improve the achievements of every peer, it is necessary to have good human resources and have high potential to be able to increase the productivity results of a company.The purpose of this study was to determine the Impact of Work Period, Work Experience, Work Ability on the Performance of Employees of PT Saka Agung Abadi Cabang Singaraja. The analysis techniques used in this study are the validity and reliability test, multiple linear regression analysis, classic assumption test, multiple correlation analysis, determination analysis, F-Test and T-Test. The results showed that Work Experience had an effect on Employee Performance at PT Saka Agung Abadi Cabang Singaraja of 0.177 units or 12.8% with a correlation value of 0.609 and the results of hypothesis testing with the T-Test test found that t-count> t-table ( 2,045> 1,687), Work Ability on Employee Performance at PT Saka Agung Abadi Cabang Singaraja has a regression value of 0.319 units or 29.0% with a correlation value of 0.798 and the results of hypothesis testing with the T-Test test found that t-count> t -table (2,563> 1,687), Working Period influences Employee Performance at PT Saka Agung Abadi Cabang Singaraja of 0.367 units or 33.7% with a correlation value of 0.807 and the results of hypothesis testing using the T-Test show that t-count> t-table (2.969> 1.687), with the results of the F-count> F-table, (33.819> 3.25). The results of this study indicate a positive influence of the Working Period, Work Experience, Work Ability on the Performance of Employees of PT Saka Agung Abadi Cabang Singaraja